Model Komunikasi Sinergis Berbasis Islam dan Penanggulangan Kejahatan Seksual terhadap Anak - Gadafi, Muamal; Amin, Hasriany (Jurnal Komunikasi Islam, 2017)
The emergency of sexual violence against children in Indonesia is considered to involve religious intervention for resolution. This article discusses the role of Islamic teachings in creating individual, social, cultural, and contextual forces as factors affecting synergetic communication for children, which further contributes to minimizing sexual abuse against children. This article argues that Islamic teachings such as introducing the masculine and feminine souls towards children in the early age, introducing the concept of aurat and sexual education to children as well as providing qishas or diyat punishment for child sexual offenders, will be able to contribute to creating societal and individual forces for their social communication skills that can protect them form predators of sexual abuse.